FONOTAKTIK BAHASA TOBA - Elisten Parulian Sigiro (Balai Bahasa Sulawesi Tengah, 2013)
This paper examines vowel, consonants, and syllables series in the Batak Toba (BT) language that aims to establish the structure of BT language phonotactics. Methods and techniques applied in this research is qualitative descriptive methods in order to reflect the fact the Batak Toba language phonotactics based on the facts that exist in the field as they are. The findings of the study show that there are the 21 series in BT vocals, in the beginning, in the middle, and in the end of the word whichhave their own part of speech such as verbs, nouns, adjectives, pronouns, and adverbs. In other side, there are 52 consonants in consonant series of BT Language.